Nik‐related kinase is targeted for proteasomal degradation by the chaperone‐dependent ubiquitin ligase CHIP. Issue 11 (1st April 2020) - Naito, Satomi; Fukushima, Toshiaki; Endo, Akinori; Denda, Kimitoshi; Komada, Masayuki
Abstract : Nik‐related kinase (Nrk) is a member of the germinal center kinase IV family and suppresses Akt signaling. In vivo, Nrk prevents placental hyperplasia and breast cancer formation. Here, we show that Nrk is regulated by the chaperone‐dependent ubiquitin ligase carboxyl terminus of heat‐shock protein (Hsp)70‐interacting protein (CHIP). Immunoprecipitation and liquid chromatography–tandem mass spectrometry analysis reveal that Nrk preferentially interacts with CHIP and Hsp70/90 family proteins. Nrk protein levels are decreased by CHIP overexpression and increased by siRNA‐mediated CHIP knockdown. Our results indicate that Nrk is ubiquitinated by CHIP in a chaperone‐dependent manner, resulting in its proteasomal degradation. CHIP targets a fraction of Nrk molecules that have lost the ability to regulate Akt signaling. We conclude that CHIP plays an important role in regulating Nrk protein levels. Abstract :